An Empirical Analysis of Block Chain Technology's Impact on Financial Inclusion in Developing Economies - Deepika, Veereedhi V.; Murty, A.V.N.; Kumar, Gaurav; Safare, Ramesh; Agasti, Nihar Ranjan; Dash, Ashok Kumar (Theoretical and Practical Research in Economic Fields, 2026)
This study examines the influence of block chain technology on financial inclusion in India from 2020 to 2025. Employing the Generalized Method of Moments (GMM) model, we analyse the relationship between block chain adoption and financial inclusion in developing nation like India, controlling for macroeconomic variables such as GDP, GDP per capita, foreign direct investment (FDI), trade openness, and institutional factors like the rule of law. The findings reveal that block chain technology has a positive and significant impact on financial inclusion, indicating that block chain innovation enhances financial accessibility and growth. However, the institutional variable, government effectiveness, does not show a considerable influence. These results underscore the role of block chain technology in promoting financial inclusion and economic development in developing economies.